A study of the response dynamics of a Helmholtz resonator and its application in acoustic energy harvesting - K.A. Omoteso; R. Marjani; O. Ozioko; O. Bagdasar; T.O. Roy-Layinde; U.H. Diala (Results in Engineering, 2025)
A thorough understanding of the behaviour of Helmholtz resonators is required for their application in noise attenuation and energy harvesting systems. This paper proposes an efficient low-frequency acoustic energy harvester (AEH) designed as a Helmholtz resonator (HR) integrated with a piezoelectric film. A straightforward continuity equation that describes the compression of air molecules in the HR's cavity was used to represent the restoring force, thus allowing us to describe the dynamics of the air molecules as a classical particle of the Duffing-type oscillator. The variation of the resonant frequency of the HR device, with its geometry, was studied, which facilitated the investigation of the response dynamics of the system, using numerical, analytical, and experimental methods. It was demonstrated that an acoustically-driven HR can also exhibit jump or hysteresis behaviour at higher acoustic pressure. The system amplifies the sound pressure within the cavity, enhancing the vibration of the piezoelectric film, thereby improving the efficiency of the energy harvesting system. A significant amount of energy was generated with the HR, about four times the value obtained without the resonator. At resonance, the acoustic energy harvester generated a maximum voltage of 84.2mV under a sound pressure level of 95dB. The results confirm the capability, efficiency, and potential of the acoustic energy harvester as a sustainable energy solution for powering low-voltage devices in various applications.